목 불안정성이 깊은목굽힘근의 기능과 목 근육들의 긴장도에 미치는 영향 - 이성현; Sung-hyun Lee; 서동권; Dong-kwon Seo (Journal of the Korean Society of Integrative Medicine, 2021)
Purpose : The time spent using smart devices is constantly increasing, particularly in recent times. Using smart devices for a long time with an incorrect posture may lead to cerebral palsy (CP), instability, and abnormal muscle tone. Therefore, we aimed to investigate the relationships among cervical instability, deep neck flexor (DNF) activity, range of motion (ROM), and muscle tonus. Methods : Fifty subjects with CP participated in this study, and they were physiotherapists at W Hospital in Daejeon. Those who voluntarily participated in the research were selected as candidates who fulfilled the selection criteria. According to an instability test, 25 subjects were assigned to the instability and control groups. All subjects first underwent the instability test to be allocated to the appropriate group. Those in the instability group tested positive on the instability test. The Neck Disability Index (NDI), ROM, muscle tone, and DNF activity were measured to evaluate their relationships. The DNF strength and endurance were measured using a cranio-cervical flexion test. The upper trapezius (UT), sternocleidomastoid (SCM), and suboccipital (SO) muscle tones were measured using a contact soft tissue tone measuring instrument. The statistical significance level was set to .05. Results : There were significant differences in the flexion, extension, and rotation of the cervical ROM (CROM) between the two groups (p<.05). The SCM, UT, and SO muscle tones were significantly different between the two groups (p<.05). The DNF strength and endurance showed a significant difference between the two groups (p<.05). Conclusion : We found that there were significant increases in the CROM and muscle tone and decrease in the DNF strength and endurance in the instability group. This indicated that cervical instability is affected by the DNF strength and endurance. We may recommend DNF exercises in cases of cervical instability in clinical environments.